Dynamic Correlation Analysis Between IHSG and JII Index as Hedging and Safe Haven (2020-2025) - Rahmad Afrenal Alim; Igo Febrianto; Fajrin Satria Dwi Kesumah (Green Economics: International Journal of Islamic and Economic Education, 2025)
This study investigates the potential role of the Jakarta Islamic Index (JII) as a hedging instrument and safe haven asset against the Indonesia Composite Index (IHSG) during the period from January 2020 to April 2025, a time characterized by elevated market volatility. The main objective is to determine whether sharia-compliant stocks in Indonesia offer diversification benefits during periods of financial stress. Utilizing daily closing prices converted into log returns, the study employs the Asymmetric Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (A-DCC GARCH) model to capture time-varying correlations between JII and IHSG. Prior to applying the model, standard diagnostic tests were performed to ensure data quality, including tests for stationarity, autocorrelation, and ARCH effects.Empirical results reveal a persistently high correlation between IHSG and JII, with an average of 0.826 and values exceeding 0.95 during periods of market turbulence. These findings indicate that JII does not fulfill the characteristics of a hedge or safe haven asset. A robustness analysis using extended data from 2010 to mid-2025 further supports the conclusion, showing the continued presence of strong comovement between the two indices across different market regimes. This suggests a structural relationship rather than one driven solely by crisis events. The high correlation may be attributed to overlapping index constituents and similar investor responses to market shocks. These results challenge the prevailing notion that Islamic indices inherently offer protection during downturns. As such, investors seeking to mitigate portfolio risk may need to look beyond domestic sharia equities and consider broader asset classes or international diversification. Future research is encouraged to explore cross-market and multi-asset safe haven properties, especially in the context of emerging economies.